Implementasi Akad Murabahah dalam Perspektif Hukum Syariah dan Pengaruhnya terhadap Profitabilitas Bank Syariah di Indonesia - Ramadhani, Ainiyya (Maliki Interdisciplinary Journal, 2025)
This article discusses the implementation of the murabahah contract from a sharia legal perspective and its impact on the profitability of Islamic banks in Indonesia. Murabahah is the most dominant financing used in Islamic banking operations because it provides income certainty through fixed margins and is easy to implement. This study uses a qualitative approach with a comparative analysis method conducted through a literature review of the fiqh provisions of the four schools of thought, contemporary regulations such as the KHES and the DSN-MUI Fatwa, as well as empirical findings regarding the effect of murabahah financing on profitability. The analysis results show that murabahah has a strong sharia legal basis and plays a significant role in increasing the profitability of Islamic banks, particularly through increasing Return on Assets (ROA). However, its implementation in the field still faces challenges, including those related to the ownership of goods in the murabahah bil wakalah contract and the potential for equalizing margins with conventional interest. Therefore, strengthening sharia compliance, more effective supervision by the DPS, and diversification of financing products are needed so that Islamic banking functions can run more optimally and in line with the maqashid sharia.